POSITIVE POLITENESS AND NEGATIVE POLITENESS STRATEGIES PERFORMED BY MAIN CHARACTER OF PRIDE AND PREJUDICE NOVEL BY JANE AUSTEN - Ria Karina; Zaenal Arifin (INFERENCE: Journal of English Language Teaching, 2022)
The objective of this study is aimed to (1) know the use of positive politeness and negative politeness use by main character in Pride and Prejudice by Jane Austen and (2) identify the function of the strategies. This study was conducted by using descriptive qualitative method to describe the positive politeness and negative politeness used by main character in the novel. The instrument of this study is the writer herself by reading the novel and coding the intended data related to positive politeness and negative politeness. The result of this study shows that there are 12 positive politeness strategies and 5 negative politeness strategies used by Elizabeth Bennet, the main character in the novel. The positive politeness strategies used are St-1, St-2, St-3, St-4, St-5, St-6, St-8, St-11, St-12, St-13, St-14, and St-15. The negative strategies used are St-1, St-2, St-4, St5, and St-6. The function of positive politeness is to minimize face threatening act show speaker awareness of hearer’s needs while the function of negative politeness is to minimize burden and reduce imposition to hearer.